Perspektivy ispolzovaniya polienzimnykh preparatov pri sportivnoj deyatelnosti - Sternin, Yu. I. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The recent dope scandals have even more sharply designated the problem of search of effective and safe for health means and methods of the optimization of sports serviceability and processes of the restoration. In this connection it is quite reasonable to be asked the question: are well familiar enough and the more so available elaboration are used? About one of such elaboration, which has received the wide resonance all over the world, the author wants to tell. The question in the article is the application of enzyme preparations in sports of the maximum achievements. Enzymes are the basis of the live ability of an organism. Without their participation are impossible neither the metabolism, nor the protection of an organism against injuring influence of physical and chemical and biological factors. The author gives some practical advices in the summary table on the application of polyenzyme preparations.